Spatial analysis of mobile phone application usage among government pensioners in Perlis / Wan Qurratu Marsha Wan Zulmajdi - Wan Zulmajdi, Wan Qurratu Marsha (2023)
This research discusses the spatial analysis of the use of mobile phone applications among government pensioners in Perlis using the Geographical Information System (GIS). Various mobile phone applications that have been introduced to the community to facilitate daily affairs. However, there are some parties who are marginalized in using this mobile phone application, namely the older group. One of the purposes of this study was to show the level of use of mobile phone applications among government pensioners in Perlis according to their respective parliaments, namely Padang Besar, Kangar and Arau. The data is obtained from the respondent's questionnaire. The raw data of government pensioners obtained from the respondent's questionnaire then successfully produced a map showing the spatial distribution of the government pensioners community in Perlis. Through the map, we can see the highest and lowest distribution of government pensioners in Perlis in the use of mobile phone applications. The results of the study show that the pensioners in Kangar and Arau parliament recorded the highest percentage in the use of mobile phone applications at 69% while the pensioners in Padang Besar parliament had the lowest use of mobile phone applications at 31%.